HARDWARE AND SOFTWARE SYSTEM OF LIGHT VISUALIZATION OF SOUND SIGNALS (Computer systems and information technologies, 2022)
The paper proposes a hardware and software system for light visualization of sound signals. The paper goes through performance requirements, system design process and practical solutions for audio visualization. The paper differs from the present solutions because it not only shows the end results, but also goes through design process, decision-making and performance measurements.There are many methods that are practically used for audio visualization: amplitude visualization, spectral visualization, frequency visualization etc. One of the most interesting and common methods is spectral visualization of audio signals. This method is based on a mathematical model of obtaining the frequency spectrum of an audio signal using fast Fourier transform (FFT) and subsequent visualization of this spectrum.The proposed solution is designed with high performance and low latency in mind and shows practical applications of hardware and software-based optimization techniques. Also, the paper describes several visualizations technics and gives an overview on possible visualization improvements.
Keywords: hardware and software; performance; audio signal visualization; fast Fourier transform (FFT); analog signal processing